Responses of Epibranchial Placodes to Disruptions of the FGF and BMP Signaling Pathways in Embryonic Mice - Washausen, Stefan; Knabe, Wolfgang (Frontiers in Cell and Developmental Biology, 2021)
Placodes are ectodermal thickenings of the embryonic vertebrate head. Their descendants contribute to sensory organ development, but also give rise to sensory neurons of the cranial nerves. In mammals, the signalling pathways which regulate the morphogenesis and neurogenesis of epibranchial placodes, localised dorsocaudally to the pharyngeal clefts, are poorly understood. Therefore, we performed mouse whole embryo culture experiments to assess the impact of pan-fibroblast growth factor receptor (FGFR) inhibitors, anti-FGFR3 neutralising antibodies or the pan-bone morphogenetic protein receptor (BMPR) inhibitor LDN193189 on epibranchial development. We demonstrate that each of the three paired epibranchial placodes is regulated by a unique combination of FGF and/or BMP signalling. Thus, neurogenesis depends on FGF signals, albeit to different degrees, in all epibranchial placodes (EP), whereas only EP1 and EP3 significantly rely on neurogenic BMP signals. Furthermore, individual epibranchial placodes vary in the extent to which FGF and/or BMP signals (1) have access to certain receptor subtypes, (2) affect the production of Neurogenin(Ngn)2+ and/or Ngn1+ neuroblasts, and (3) regulate either neurogenesis alone or together with structural maintenance. In EP2 and EP3, all FGF-dependent production of Ngn2+ neuroblasts is mediated via FGFR3 whereas, in EP1, it depends on FGFR1 and FGFR3. Differently, production of FGF-dependent Ngn1+ neuroblasts almost completely depends on FGFR3 in EP1 and EP2, but not in EP3. Finally, FGF signals turned out to be responsible for the maintenance of both placodal thickening and neurogenesis in all epibranchial placodes, whereas administration of the pan-BMPR inhibitor, apart from its negative neurogenic effects in EP1 and EP3, causes only decreases in the thickness of EP3. Experimentally applied inhibitors most probably not only blocked receptors in the epibranchial placodes, but also endodermal receptors in the pharyngeal pouches, which act as epibranchial signalling centres. While high doses of pan-FGFR inhibitors impaired the development of all pharyngeal pouches, high doses of the pan-BMPR inhibitor negatively affected only the pharyngeal pouches 3 and 4. In combination with partly concordant, partly divergent findings in other vertebrate classes our observations open up new approaches for research into the complex regulation of neurogenic placode development.